Epigenetic Histone Marks of Extended Meta-Polycentric Centromeres of Lathyrus and Pisum Chromosomes - Neumann, Pavel; Schubert, Veit; Fuková, Iva; Manning, Jasper E.; Houben, Andreas; Macas, Jiří (Frontiers in Plant Science, 2016)
Species of the legume genera Lathyrus and Pisum possess chromosomes that exhibit a unique structure of their centromeric regions, which is clearly apparent during metaphase by the formation of extended primary constrictions which span up to a third of the length of the chromosome. In addition, these species express two different variants of the CenH3 protein which are co-localized in multiple domains along the poleward surface of the primary constrictions. Here we show that the constrictions represent a distinct type of chromatin differing from the chromosome arms. In metaphase, histone phosphorylation patterns including H3S10ph, H3S28ph and H3T3ph were observed along the entire constriction, in a way similar to holocentric chromosomes. On the other hand, distribution of phosphorylated H2AT120 was different from that previously reported from either, holocentric and monocentric chromosomes, occurring at chromatin surrounding but not overlapping CenH3 domains. Since some of these phosphorylations play a role in chromatid cohesion, it can be assumed that they facilitate correct chromosome segregation by ensuring that multiple separate CenH3 domains present on the same chromatid are oriented towards the same pole. The constrictions also displayed distinct patterns of histone methylation marks, being enriched in H3K9me2 and depleted in H3K4me3 and H3K27me2 compared to the chromosome arms. High resolution fluorescence microscopy revealed that although both CenH3 protein variants are present in all CenH3 domains detected on metaphase chromosomes, they are only partially co-localized while there are chromatin subdomains which are mostly made of only one CenH3 variant. Taken together, these data revealed specific features of extended primary constrictions of Lathyrus and Pisum and support the idea that they may represent an intermediate stage between monocentric and holocentric chromosomes.